Licenciatura em matemática das universidades estaduais da Bahia: origem e estado atual - Mattos, Robson Aldrin Lima (2016)
The work brings the origin and current state of Degree Courses in Mathematics of the Bahia State Universities. It is part of the education area, the theme of Mathematics Education in the line of research "Mathematics in the Curriculum Structure and Teacher Training" of the PEPGEM-PUC / SP and in the project "Documentary searches related to articulations of the/in the Mathematics: knowledge of teacher and influences in Basic Education ". The main objective of the thesis is to present the legal bases of Degree Courses in Mathematics of the Bahia State Universities, as well as bringing out menus and flowcharts of their Pedagogical Policy Projects. From a methodological point of view, it is a case study, for its uniqueness with a qualitative approach on the documents examined. It focuses on curriculum components: Mathematics Education and Mathematics, by the extent of the material of the universities and with the support of publications in Mathematics Education, analyzes their menus. Therefore, it presents a comparative summary about what these courses offer as a whole. As a result we can see that the Degree Courses in Mathematics of UEBA are very close when it refers to the Mathematics Education field. The curriculum components related to teaching converge in the same direction. In the supervised training field, the Degree courses in Mathematics are similar with regard to teacher training to Primary Education and High School. With regard to the Mathematics field, the Degree courses go in a specific way and are more targeted to the pedagogical practice of future career in education